Pengaruh Ukuran Perusahaan, Solvabilitas dan Laba Rugi Terhadap Audit Delay pada Perusahaan Menufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2020 - Lase, Yuli Rista; Syafitri, Yulia; Ayu Putri, Sri Yuli (Fakultas Ekonomi, Universitas Ekasakti, 2024)
This study aims to examine the effect of firm size, solvency and profit and loss on audit delay in manufacturing companies listed on IDX for the 2019-2020 period. The population of this study consisted of 175 manufacturing companies listed on the Stock Exchange and the sampling method using purposive sampling. With this method, a sample of 26 companies was obtained with an observation period of 2 years (2019-2020) so that the number of observations was 52. The audit delay variable was measured by the date of issue of the financial statements minus the date of issue of the auditor's report, the size of the company was measured by Ln total assets, solvency is measured by using debt to asset ratio and profit and loss is measured by Ln value of profit and loss. The data used in this research is quantitative data. The data collection technique used in this research is the documentation method and the internet web. The data analysis technique used multiple linear regression analysis. The results showed that: 1) firm size had a significant effect on audit delay, 2) solvency had a significant effect on audit delay, 3) profit and loss had no significant effect on audit delay, 4) firm size, solvency and profit and loss simultaneously had a significant effect on audit. Delay.